Analisis Asset Intensity, Profitability, dan Leverage Terhadap Cost Stickiness - Prawesti, Disa Muqiita; Ariani, Kurnia Rina (Jurnal EMT KITA, 2024)
This study aims to analyze the effect of asset intensity, profitability, and leverage on cost stickiness in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The research method employed is a quantitative approach, with a population of 144 companies, from which a sample of 70 companies was selected using purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that asset intensity and profitability have a significant effect on cost stickiness, while leverage does not have a significant effect. These findings provide additional insights into cost behavior within companies and can serve as a reference for further research in managerial accounting. Moreover, the results of this study are expected to assist management in making more effective decisions regarding cost control.